2012
DOI: 10.1002/j.2051-3909.2012.tb00172.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of medical imaging technologists on use of gonad shielding in general radiography

Abstract: Purpose: Gonad shielding is an important way to address the ‘as low as reasonably achievable’ (ALARA) requirement in radiography. However, its use relies on the attitudes of medical imaging technologists (MITs) to consistently adhere to professional conduct requirements relating to the application of gonad shielding. The purpose of this study was to investigate the attitudes of Western Australian (WA) MITs to the use of gonad shielding in general radiography and also to explore the variables influencing these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…However, some studies suggested that gonad shields can be omitted in the first pelvic radiographs to prevent covering important anatomical data (13). Other studies suggested that the provision of gonad shielding guidelines in radiology departments could improvements its application (4,7,(16)(17)(18). However our results were based on direct observation in which gonads were directly and indirectly exposed.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, some studies suggested that gonad shields can be omitted in the first pelvic radiographs to prevent covering important anatomical data (13). Other studies suggested that the provision of gonad shielding guidelines in radiology departments could improvements its application (4,7,(16)(17)(18). However our results were based on direct observation in which gonads were directly and indirectly exposed.…”
Section: Discussionmentioning
confidence: 75%
“…The results of this study are worrying as the importance of gonad shielding has been well established in the literature (4,6,11). It seems that, in procedures in which gonads are exposed in the primary beam, it is difficult to correctly position the gonad shields so that gonads are completely obscured whilst not concealing important anatomical data (4,6,7,11). MacKay et al (2012) believed that "one of the main reasons for omission of the gonad shield is a lack confidence or skill in the gonad shield placement of radiographers and the attitude that gonad shielding is not applied to patients whilst not compromising the diagnostic quality of the image" (7).…”
Section: Discussionmentioning
confidence: 88%
“…Dose reduction methods for all abdominal organs are essential since they cannot be shielded. Similarly the use of lead rubber shielding for the testes and ovaries is often omitted due to difficulties with accurate placement (22), especially during the lateral projection. Poor positioning of gonad protection can create artefacts on images which may obscure important anatomical data or pathology and result in a repeat examination being required (3).…”
Section: Discussionmentioning
confidence: 99%
“…The low adherence rate of radiographers applying lead shields is reported to result from the complexity in identifying gonadal position in relation to surface landmarks and the risk of obscuring bony structures. 5,24,25 Our developed bismuth ovarian shield protects the ovaries, colon, and pelvis bone by covering the entire pelvic region. Because bismuth shields can be placed more easily without concern for obscuring diagnostic features, these developed shields are easier to use, especially in crowded and emergency radiology centres.…”
Section: Discussionmentioning
confidence: 99%